Fraction-resolved pyrolysis behavior, conversion-dependent kinetics, and predictive severity framework for engineered biochars from fig-processing residues - Soomro, Ahsanullah; Kocer, Anil Tevfik; Balkanli, Didem (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Industrial fig processing generates seed-rich and skin-rich residues that remain underutilized as biochar precursors. This study treated fractionation as a process-design variable by comparing separately recovered fig seed and fig skin under matched pyrolysis conditions and multi-rate thermogravimetric analysis. Across a severity matrix of 350-500 degrees C with varied heating rates and holding times, biochar yield decreased from 30.3 to 24.52% for fig seed and from 32.0 to 27.73% for fig skin, with fig skin consistently retaining more solid under identical programmes. ATR-FTIR analysis revealed different carbonization pathways: seed-derived chars showed stronger attenuation of O-H and aliphatic C-H bands together with a more pronounced condensed/aromatic region, whereas skin-derived chars retained clearer oxygen-containing features. TG-DTG analysis at 5-40 degrees C min(-1) showed contrasting devolatilization behavior, with fig seed dominated by a broad mid-temperature event and fig skin characterized by an early dominant peak followed by a secondary higher-temperature contribution. Gaussian DTG-stage partitioning converted these differences into quantitative descriptors, with fig skin retaining a persistent Stage I contribution ( = 400 degrees C; up to 52.17%). Isoconversional analysis showed higher and more conversion-sensitive apparent activation energies for fig seed (similar to 107-327 kJ mol(-1)) than for fig skin (similar to 74-151 kJ mol(-1)). DAEM analysis supported this contrast, while screening gate-to-gate LCA showed that midpoint burdens were governed mainly by programme-level electricity demand, with Program 3 giving the lowest burdens for both fractions. These results support a fraction-specific severity framework for targeted biochar production.
Keywords: Fig-processing residues; Biochar; Pyrolysis; Isoconversional kinetics; Distributed activation energy model; Life-cycle assessment; ACTIVATION-ENERGY MODEL; THERMOGRAVIMETRIC ANALYSIS; MASTER PLOTS; BIO-OIL; BIOMASS; CARBONIZATION; CELLULOSE; NUMBER; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels